1999
DOI: 10.4065/74.9.890
|View full text |Cite
|
Sign up to set email alerts
|

Appendiceal Diverticulitis

Abstract: Diverticulitis has long been known to affect the right colon, and in recent years, our understanding has evolved in regard to the underlying cause. Appendiceal diverticulitis has yet to gain widespread recognition despite the fact that it was first described in 1893. Commonly dismissed by surgeons and pathologists as a variant of true appendicitis, appendiceal diverticulitis is a discrete clinical process that must be considered in the appropriate setting. We describe a case of appendiceal diverticulitis in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 9 publications
0
55
0
Order By: Relevance
“…The degree of inflammation in the appendiceal wall apart from the diverticula was lower than that of acute appendicitis in the current series. Phillips et al [5] report that 5 microscopic types of diverticular disease of the appendix can be defined as (1) primary acute diverticulitis, with or without acute peridiverticulitis, (2) acute diverticulitis secondary to acute appendicitis, (3) diverticulum without inflammation, (4) diverticulum with acute appendicitis, and (5) chronic peridiverticulitis with acute appendicitis. Inflammatory cells were localized in the diverticulum of the appendix in 6 out of the 12 cases, corresponding to the type of primary acute diverticulitis, with or without acute peridiverticulitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The degree of inflammation in the appendiceal wall apart from the diverticula was lower than that of acute appendicitis in the current series. Phillips et al [5] report that 5 microscopic types of diverticular disease of the appendix can be defined as (1) primary acute diverticulitis, with or without acute peridiverticulitis, (2) acute diverticulitis secondary to acute appendicitis, (3) diverticulum without inflammation, (4) diverticulum with acute appendicitis, and (5) chronic peridiverticulitis with acute appendicitis. Inflammatory cells were localized in the diverticulum of the appendix in 6 out of the 12 cases, corresponding to the type of primary acute diverticulitis, with or without acute peridiverticulitis.…”
Section: Discussionmentioning
confidence: 99%
“…While diverticulum of the appendix has been frequently reported in Europe and the United States, the incidence of congenital diverticulum of the appendix and acquired diverticulum of the appendix are 0.014% and 0.20 to 1.7%, respectively [3]. Previous authors have suggested that a diverticulum of the vermiform appendix has a higher risk of perforation than acute appendicitis [4][5][6][7][8][9][10]. This report reviewed 12 cases of appendiceal diverticulitis admitted to a single institution over a 4-year period.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The acquired lesions occur on the mesenteric border of the appendix in association with an arteriolar vessel. Appendiceal diverticulae have been classified in four subtypes [6]. Type 1 is a normal appearing appendix with an acutely inflamed diverticulum.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital (or true) diverticula are exceedingly rare (less than 50 cases have been reported) (2) . Acquired pseudodiverticula, characterized by herniation of the mucosa and submucosa through a defect in the muscular layer, have a reported incidence ranging from 0.04 to 2.8% (1,3) .…”
Section: Case Reportmentioning
confidence: 99%